Technological Innovation Fintech in Accounting Information System Development: Case Study of Micro, Small and Medium Enterprises (MSMEs) in Gonilan Village - Farika, Devina Widya; Achyani, Fatchan (Islamic Business and Management Journal, 2024)
This study aims to analyze the impact of financial technology (FinTech) innovation on the accounting information systems of Micro, Small, and Medium Enterprises (MSMEs) in Gonilan Village. The research employed a descriptive qualitative approach with data collection techniques including interviews, observation, and documentation. The results indicate that the adoption of QRIS enhances transaction efficiency, financial record accuracy, and business branding. However, challenges such as dependence on internet connectivity and the risk of fraud remain obstacles. This study provides recommendations for training and infrastructure improvements to support the digital transformation of MSMEs. Keywords: FinTech, QRIS, Accounting Information System, MSMEs